QUANTUM CHEMICAL CALCULATIONS OF SOME BENZENE DERIVATIVES - Fatma Kandemirli; Fatma Genç (Journal of Amasya University the Institute of Sciences and Technology)
HOMO-LUMO energies, hardness, Mulliken, electronic and zero-point energy, Mulliken charges of benzene, fluorobenzene, chlorobenzene, bromobenzene, nitrobenzene, cyanobenzene, trifluoromethyl benzene, ethenylbenzene, di, tri, tetra and penta fluorobenzene molecules in gas phase and water phase for neutral and anionic form were calculated with B3lyp/6-31G(d,p) level by using G03 program and also hybridization of these molecules were studied. The Sum of electronic and zero-point energies found from the calculations performed in the gas phase is lower than made in the water phase.